Alkaline-earth and aminonicotinate based coordination polymers with combined fluorescence/long-lasting phosphorescence and metal ion sensing response. Issue 23 (22nd May 2019) - Pajuelo-Corral, Oier; Rodríguez-Diéguez, Antonio; Beobide, Garikoitz; Pérez-Yáñez, Sonia; García, Jose A.; San Sebastian, Eider; Seco, Jose M.; Cepeda, Javier
Abstract : Alkaline-earth and aminonicotinate based CPs exhibit green long lasting phosphorescence and bright blue fluorescence responsive to metal ions. Abstract : Six novel coordination polymers (CPs) based on alkaline-earth (AE) metal ions and two sorts of aminonicotinate ligands, namely [M(μ-2ani)(μ3 -2ani)(μ-DMF)] n [M II = Sr (1 ) and Ba (2 )], {[M(μ-6ani)2 (H2 O)2 ]·3H2 O} n [M II = Ca (3 ) and Sr (4 )], {[Ca(μ-6ani)2 (H2 O)2 ]} n (5 ) and {[Ba(6ani)2 (H2 O)3 ]·7H2 O} n (6 ) [where 2ani = 2-aminonicotinate and 6ani = 6-aminonicotinate] have been synthesized and well characterized. All compounds are firstly built up with AE-carboxylate infinite rods that provide compact 2D-layered structures in1 and2 but open architectures containing microchannels in an AE-6ani system. Interestingly, the architecture of3 behaves as a flexible platform which undergoes spontaneous dehydration to yield compound5 . Structural transition occurring from3 to5 has been supported by periodic density functional theory (DFT) calculations and X-ray diffraction data. In this regard, compound6 contains a high amount of solvent molecules which suggests the existence of pores in its structure. A deep study of the optical properties including a detailed experimental characterization and DFT based computational calculations of these compounds supports a fascinating photoluminescence performance which entails a bright blue emission accompanied by persistent green afterglows at low temperature, especially for compound5 as reflected by its lifetime ( τ ≈ 1.4 s). In addition to its strong room temperature emission properties, we took advantage of the open yet stable structure of compound4, to check its viability as a new material sensitive to the presence of solvents and/or transition metal ions, via significant quenching of the luminescence of4 . Remarkably, 4 is shown to be a particularly efficient sensor for some water soluble pollutants.